If h(m+n) = m(h+r) find h in terms of m, n and r
...If h(m+n) = m(h+r) find h in terms of m, n and r
h=mr2m+n
h=mrn+m
h=m+nn
h=m+nm
h=mrn
Correct answer is E
h(m+n)=m(h+r)hm+hn=hm+mrhn=mrh=mrn
The area of a square is 144 sq cm. Find the length of its diagonal ...
Find the median of the set of numbers 110, 116, 113, 119, 118, 127, 118, 117, 113 ...
The volume of a hemispherical bowl is 71823. Find its radius . ...
The solution of the quadratic inequality (x3 + x - 12) ≥ 0 is...
Find the mean deviation of 6, 7, 8, 9, 10 ...
Arrange in ascending order of magnitude 268,367,and259...
In the diagram, ¯MN//¯PQ, < MNP = 2x, and < NPQ = (3x - 50)°. ...